Turkish Neonatal Society guideline on parenteral nutrition in preterm infants - (:unkn) unknown (TURKISH PEDIATRICS ASSOC, 2019)
Postnatal growth failure due to inappropriate and insufficient nutrition is a risk for preterm infants, especially for very-low-birth-weight or extremely-low-birth-weight infants. This extrauterine growth failure causes negative effects on long-term neurodevelopment. Early initiation of intensive parenteral nutrition with appropriate protein and energy supply is a nutritional emergency when enteral feeding cannot be achieved. This approach prevents protein catabolism and helps achievement of positive protein balance and postnatal growth. Protein, lipid, and glucose initiation with appropriate doses that reach timely goals constitute the major elements of parenteral nutrition. The transition to enteral nutrition with the mother's milk at the earliest convenience must be targeted in parenteral nutrition.
Keywords: Feeding; parenteral nutrition; preterm; BIRTH-WEIGHT INFANTS; SUPPORT PRACTICE GUIDELINES; LIPID EMULSIONS; CARE; GROWTH; RECOMMENDATIONS; REQUIREMENTS; MALNUTRITION; COMMITTEE; OUTCOMES